Estimulación temporo-espacial en el desarrollo de la motricidad gruesa de los niños y niñas de Educación Inicial II del Centro particular “Benjamín Franklin”. - Granizo Valdiviezo, Mónica Elizabeth (2024)
This research was carried out with the children of the “Benjamín Franklin” Private Early Education Center in the City of Riobamba (Ecuador), with temporal-spatial stimulation being of great importance in the development of gross motor skills, as it strengthens their abilities and skills. for better emotional control, tranquility and increased mental capacity when acquiring new learning. The main objective of this research was to determine the contribution of Temporo-Spatial Stimulation in the development of Gross Motor Skills. A quantitative approach methodology was used, with a quasi-experimental research design with a control group and pretest, the research technique used was observation and the instrument applied was the observation sheet, previously validated. The population was made up of 20 children of initial education II, to whom the pretest was applied, subsequently the activities were carried out with the implementation of the children's games guide and at the end the post test was applied to both the experimental group and the control group. , to verify the advances generated by Temporo-Spatial Stimulation. When analyzing the results obtained, the children who were part of the experimental group reached adequate levels in their gross motor development. It was concluded that temporal-spatial stimulation with the help of recreational activities is important for the development of participatory skills, strengthening the gross motor skills of students.